(untitled) - Ching, Francis D. K (New York, 2003)
Architectural Graphics presents a wide range of basic graphic tools and techniques designers use to communicate architectural ideas. Expanding upon the wealth of illustrations and information that have made this title a classic, this Fourth Edition provides expanded and updated coverage of drawing materials, multiview drawings, paraline drawings, and perspective drawings. Also new to this edition is the author's unique incorporation of digital technology into his successful methods. While covering essential drawing principles, this book presents: approaches to drawing section views of building interiors, methods for drawing modified perspectives, techniques for creating accurate shade and shadows, expert styles of freehand sketching and diagramming, and much more.
Keywords: Architectural drawing,Đồ hoạ kiến trúc